Pengembangan Industri Jamur Tiram dan Buah Naga dalam Menjaga Pluralitas dan Keberagaman Desa Kesilir Kecamatan Siliragung Kabupaten Banyuwangi - Mahmudah Mahmudah; Nawal Ika Susanti (IAI Darussalam, 2020)
Kesilir Village is a village famous for its Dragon Fruit paradise, located in Siliragung District, Banyuwangi Regency. This village has 3 hamlets namely Sumbersuko, Sumberbening and Silirsari hamlets. General conditions of assistance 1) The number of Oyster Mushroom farmers who are not developing their business; 2) Most of the Oyster Mushroom Farmers did not continue their business; 3) The reduced stock of Oyster Mushrooms in the market; 4) Lack of creativity of Oyster Mushroom farmers to innovate their products; 5) Less innovation in Dragon Fruit Processing; 6) Many Dragon Fruit farmers suffer losses; 7) Most of the youth only rely on laborers. After the utilization of oyster mushrooms and dragon fruit lunkhead followed by the Sumberbening youths united, the community felt very helpful in solving these annual problems such as if the price of Dragon fruit decreased and there was less innovation in the processing of Oyster Mushrooms. This program received a positive response from the youth of Sumberbening because of the increasing economic problems of the community so that this activity could be used as a home industry that unites differences and can increase the income of the surrounding community